+0  
 
0
49
1
avatar+1380 

Help.

NotSoSmart  Jan 3, 2018
Sort: 

1+0 Answers

 #1
avatar+81022 
+1

21.   Rearrange as

 

x^4 + 27x^2 - 324  =  0       factor as

 

(x^2  -  9)  ( x^2  + 36)  = 0

 

(x + 3) ( x - 3)  ( x + 6i) (x - 6i)  = 0

 

Set each factor to 0 and solve for x and we get the solutions  x = -3, 3, - 6i, 6i

 

 

22.  ( s +  3v)^5   =

 

s^5   +  5*s^4*(3v)  + 10*s^3*(3v)^2  +  10*s^2*(3v)^3  + 5*s*(3v)^4  + (3v)^5  =

 

s^5  + 15s^4v + 90s^3v^2  + 270s^2v^3 + 405sv^4  + 243v^5

 

 

cool cool cool

CPhill  Jan 3, 2018

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details